Down-Regulation of Progesterone hormone in Recurrent pregnancy Loss - Hussain, Alaa Gani; Al-Obaidi, Asmaa’ Baqer; Salman, Amal Hussain (Journal of the Faculty of Medicine Baghdad, 2008)
Background:Progesterone hormone is important in the preparation for and in maintaining of pregnancy through different mechanisms but mainly by shifting the balance from Th1 to Th2 mediatedimmunity to avoid rejection of the fetus; in this study we tried to find out whether there is a relation between the level of the expression of progesterone and its stimulant HCG hormone and recurrent pregnancy loss (RPL).Patients and Methods:Immunohistochemistry technique was performed to detect and determine the expression of progesterone and HCG hormones using paraffin embedded sections of curate samples obtained from 40 women, who where divided into three groups: 24 women with RPL, 10 women with abortion for the first time, and 6 women with induced abortion.Results:The levels of the expression of both progesterone and HCG hormones were found to be significantly down-regulated in the first group as compared with the second group (p=0.00), andthe third group (p=0.00), with a highly significant positive correlation between these two parameters (r=0.866, p